2019
DOI: 10.1093/europace/euz056
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of atrial maze surgery in patients with congenital heart disease

Abstract: Aims Recurrent atrial tachycardia is common after repair of many types of congenital heart disease, and surgical ablation with a maze procedure represents a potential treatment strategy. The objective of this study is to report a single-centre 19 years’ experience with maze surgery in congenital heart patients. Methods and results Patients undergoing maze procedure concomitantly with cardiac surgical procedures were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Prophylactic surgical ablation has been reported for “high-risk” (such as rheumatic heart disease patients undergoing MV repair) procedures. 32 As these high-risk patient populations are rarely found within the United States, however, this prophylactic approach to prevent AF is not commonplace. PAF in the field of MV disease has great potential to reduce the incidence of PAF, reduce mortality, and improve the quality of life for patients undergoing MVS due to the high incidence of PAF in these patients and opportunities for concomitant prophylactic ablative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic surgical ablation has been reported for “high-risk” (such as rheumatic heart disease patients undergoing MV repair) procedures. 32 As these high-risk patient populations are rarely found within the United States, however, this prophylactic approach to prevent AF is not commonplace. PAF in the field of MV disease has great potential to reduce the incidence of PAF, reduce mortality, and improve the quality of life for patients undergoing MVS due to the high incidence of PAF in these patients and opportunities for concomitant prophylactic ablative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 Europace study reported on a single-centre’s 19 years’ experience with maze surgery in patients with CHD. 60 In this study, the maze procedure was classified as therapeutic if the patient demonstrated preoperative atrial arrhythmias, or as prophylactic if done because the patient was considered high risk for postoperative arrhythmias. A maze was performed on 137 subjects in the therapeutic group and 29 in the prophylactic group.…”
Section: Adult Congenital Heart Diseasementioning
confidence: 99%
“…Atrial tachyarrhythmia commonly occurs in patients with adult congenital heart disease (ACHD) due to atrial volume, pressure overload, and surgical scars. 1 , 2 Atrial tachyarrhythmias can cause a deterioration in the quality of life and lead to heart failure and hospitalizations. 3 , 4 , 5 , 6 , 7 Therefore, it is essential to manage the cumulative lifetime risk of atrial tachyarrhythmia.…”
mentioning
confidence: 99%
“…Previous studies have reported that the age at the time of arrhythmia surgery, duration of arrhythmia, Ebstein anomaly, and tetralogy of Fallot (TOF) were risk factors for atrial arrhythmia recurrence. 1 , 8 …”
mentioning
confidence: 99%